Isolation and identification of lactic acid bacteria from traditional food sarobuong of Kuantan Singingi District, Riau, Indonesia - SARYONO SARYONO; ISMAWATI ISMAWATI; NOVA WAHYU PRATIWI; SILVERA DEVI; MERRY YOHANA SIPAYUNG; NABELLA SURAYA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saryono, Ismawati, Pratiwi NW, Devi S, Sipayung MY, Suraya N. 2023. Isolation and identification of lactic acid bacteria from traditional food sarobuong of Kuantan Singingi District, Riau, Indonesia. Biodiversitas 24: 2201-2206. Lactic acid bacteria (LAB) are commonly used as probiotic agents in fermented processed foods like sarobuong. Sarobuong is a traditional food from Kuantan Singingi District made by fermenting bamboo shoots. In this study, the isolation and purification of LAB from sarobuang were done using MRS agar media with the streak quadrant method: macroscopic and microscopic observations and biochemical and physiological tests to identify isolates. The antibacterial ability of LAB isolates was used against pathogenic bacteria Escherichia coli and Staphylococcus aureus. The results showed that 21 isolates were gram-positive bacteria in the form of bacilli and coccus, while carbohydrate degradation was homofermentative. The results of the antibacterial test of 21 isolates indicated by LAB against E. coli and S. aureus bacteria showed a clear zone ranging from 0.1 to 0.6. The highest antibacterial activity against pathogenic bacteria E. coli was observed in isolate RB1, while for pathogenic bacteria S. aureus, it was in isolate R15. The results obtained from several isolates that have been tested showed that LAB isolated from sarobuong had relatively higher activity than the control and was identified as Lactobacillus and Streptococcus.